Parametric study of high-energy ring-shaped electron beams from a laser wakefield accelerator. (3rd February 2022) - Maitrallain, A; Brunetti, E; Streeter, M J V; Kettle, B; Spesyvtsev, R; Vieux, G; Shahzad, M; Ersfeld, B; Yoffe, S R; Kornaszewski, A; Finlay, O; Ma, Y; et al.
Abstract: Laser wakefield accelerators commonly produce on-axis, low-divergence, high-energy electron beams. However, a high charge, annular shaped beam can be trapped outside the bubble and accelerated to high energies. Here we present a parametric study on the production of low-energy-spread, ultra-relativistic electron ring beams in a two-stage gas cell. Ring-shaped beams with energies higher than 750 MeV are observed simultaneously with on axis, continuously injected electrons. Often multiple ring shaped beams with different energies are produced and parametric studies to control the generation and properties of these structures were conducted. Particle tracking and particle-in-cell simulations are used to determine properties of these beams and investigate how they are formed and trapped outside the bubble by the wake produced by on-axis injected electrons. These unusual femtosecond duration, high-charge, high-energy, ring electron beams may find use in beam driven plasma wakefield accelerators and radiation sources.